The Role of Apron Movement Control Unit Officers in Handling the Movement of Cargo Planes at the Tjilik Riwut Palangkaraya Airport Apron - Stefanus Leonardo Sandan (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
The purpose of this study is to study; (1) What are the roles of AMC officers inhandling the  movement of cargo aircraft on apron Bandar Udara Tjilik Riwut Palangkaraya? ; (2) What are the obstacles faced and solutions for AMC officers in handling the movement of cargo aircraft on apron Bandar Udara Tjilik Riwut Palangkaraya? . The research method used is a qualitative method with an interview and observation approach. The results showed that; (1) The role of AMC officers inhandling the movement of  cargo aircraft on apron Bandar Udara Tjilik Riwut Palangkaraya as  follows: (a) Regulate the movement and placement of aircraft so as not to collide with other aircraft.  (b) Regulate the movement and placement of aircraft so that they do not collide or be obstructed by obstacles in the apron and its surroundings.   (c) Regulate the placement of aircraft on the parking stand based on the type and size of the aircraft.  (d) Regulate the entry and exit of aircraft from the apron (parking stand) to the manoeuvring area or vice versa. In this case, coordination must be carried out with the Aerodrome Control Tower unit in advance. (e) Ensure the safety and smooth movement of vehicles and the regularity of other activities on the apron. (2) Obstacles faced by AMC officers in handling the movement of cargo aircraft on the apron of Tjilik Riwut Airport Palangkaraya include; (a) Lack of personnel or human resources, (b) Lack of Quality and Quantity of CCTV compared to the apron area, (c) Does not have a remote area for all types of aircraft, (d) Parking stand Constraints for unscheduled flights, (e) Lack of Communication in AMC Officer Shift Changes.  Solutions to  the obstacles faced by AMC officers in handling the movement of cargo aircraft on apron Bandar Udara Tjilik Riwut Palangkaraya, including; (a) Addition of personnel or human resources, (b) Improvement of Quality and Quantity of CCTV in proportion to the area of ap ron, (c) Determination of remote areas for all types of aircraft, (d) Increase Officer Readiness in facing unscheduled flights, (e) Improve coordination and communication of AMC units.